2019 41st Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2019
DOI: 10.1109/embc.2019.8856850
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Helical Propulsion Inside In Vitro and Ex Vivo Models of a Rabbit Aorta

Abstract: In this work, the propulsion of a helical robot is experimentally characterized inside whole blood (in vitro model) and against the flowing streams of phosphate buffered saline (PBS) inside rabbit aorta (ex vivo model). The helical robot is magnetically actuated inside these models under the influence of rotating magnetic fields. The frequency response of the helical robot is characterized. Averaged speed is measured at actuation frequency of 8 Hz as 11.3 ± 0.52 (n = 5) and 7.45 ± 1.2 mm/s (n = 3) inside rabbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…One of the advantages of employing magnetic strategies is their suitability in restricted space, allowing for wireless control in an environment that is suitable for clinical applications [13]. Untethered (magnetic) actuators have shown some potential during in vitro experiments with artificial embolisms [14], [15]. Similarly, studies have demonstrated magnetic drilling actuators [16] and characterized their locomotion and drilling performance in vascular network-mimicking fluidic channels [17] and animal brain tissue [18].…”
Section: Introductionmentioning
confidence: 99%
“…One of the advantages of employing magnetic strategies is their suitability in restricted space, allowing for wireless control in an environment that is suitable for clinical applications [13]. Untethered (magnetic) actuators have shown some potential during in vitro experiments with artificial embolisms [14], [15]. Similarly, studies have demonstrated magnetic drilling actuators [16] and characterized their locomotion and drilling performance in vascular network-mimicking fluidic channels [17] and animal brain tissue [18].…”
Section: Introductionmentioning
confidence: 99%
“…The second one is bio-inspired [8], using an analogy with the Escherichia Coli bacteria, rodhobacter spheroids, spermatozoon among others. The corkscrew-like motion and the undulating flexible flagella motion have been extensively reviewed in the literature [9,10]. Alternatively, new locomotion methods have also been proposed using magnetic torques and forces.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Alshafeei et al have proposed a method by using synchronously rotating two permanent magnets to control a helical robot in a glass tube, resulting in the establishment of a relationship between the movement speed of the helical robot and the rotation frequency of the permanent magnet [193]. Furthermore, Mahdy et al have utilized a helical robot to verify its characteristics of helical propulsion inside in vitro and ex vivo models of a rabbit aorta [194]. Moreover, Tan et al have proposed a novel fabrication method to enhance the swimming performance of helical robots by leveraging the benefits of a robust magnetic head and a flexible deformable tail [195].…”
Section: Navigation Of Untethered Small-scale Helical Devices Usingmentioning
confidence: 99%
“…Although the above works have proposed many advanced methods and equipment, there is still room for improvement. For instance, the only basic screw characteristics of helical propulsion of the robot under two synchronously rotating permanent magnets have been studied [193], [194]. Furthermore, the researcher only has studied the 1-D motion of the helical robot and implemented a clear experiment of thrombus [114], [118].…”
Section: Navigation Of Untethered Small-scale Helical Devices Usingmentioning
confidence: 99%